“Phantom” infrastructures and metropolitan development: a reflexion from Lisbon Metropolitan Area - Gonçalves, Jorge; Carvalho, Luís; Saraiva, André (AESOP, 2016)
Some infrastructures, such as seaports, airports or high-speed railway, among others, for its relevance, can generate significant, territorial and others, effects at differentiated scales. These effects begin to be felt even much before their physical implementation. Its simple announcement is enough to shake sectors such as real estate, specialized consulting or the municipal and/or regional policies. These investments, which structure the territory and even some specific sectors, are in large examples proposed in absentia of existing planning instruments or in preparation. Its public presentation represents something new, activating a set of dynamics in the private and public domains, which ultimately carry the simple announcement of a decision to the plan of concrete reality. Beyond this automatic effects, is also important to consider the difficulty to politically decide their effective implementation by either the complexity or uncertainty but also for the associated costs. The indecision, delay and, often, the retreat in the decision carries heavy costs, sometimes unrecoverable to people, activities and territories, even if dealing with an infrastructure that never had a real existence.
Proceedings of the IV World Planning Schools Congress, July 3-8th, 2016 : Global crisis, planning and challenges to spatial justice in the north and in the south